2018
DOI: 10.1021/acs.langmuir.8b01756
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polyimide Aerogels with a Uniform Nanoporous Framework

Abstract: Polyimide (PI) aerogels were successfully synthesized via a straightforward sol-gel process under room temperature along with the supercritical CO drying method using 4-amino- N-methylbenzamide and 3,3',4,4'-biphenyltetracarboxylic dianhydride. 1,3,5-Triaminophenoxybenzene was used as the cross-linker. The chemical structure, pore structure, morphology, thermal performance, CO adsorption, and mechanical performance of PI aerogels were investigated. The as-prepared PI aerogels had low bulk densities (0.091-0.16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…The welded PI-NFAs with various densities (0.96–16.14 mg/cm 3 ) were prepared simply by adjusting the concentrations of the nanofiber dispersions, and their porosities are listed in Table S3. Plotting the porosities of various PI aerogels (sol–gel-derived PI aerogels ,, and nanofiber-based PI aerogels , ) versus their density revealed that the welded PI-NFAs fabricated in this study processed much lower density and higher porosity compared to the sol–gel-derived PI aerogels and nanofiber-based PI aerogels strengthened by cross-linkers (as shown in Figure d).…”
Section: Resultsmentioning
confidence: 80%
“…The welded PI-NFAs with various densities (0.96–16.14 mg/cm 3 ) were prepared simply by adjusting the concentrations of the nanofiber dispersions, and their porosities are listed in Table S3. Plotting the porosities of various PI aerogels (sol–gel-derived PI aerogels ,, and nanofiber-based PI aerogels , ) versus their density revealed that the welded PI-NFAs fabricated in this study processed much lower density and higher porosity compared to the sol–gel-derived PI aerogels and nanofiber-based PI aerogels strengthened by cross-linkers (as shown in Figure d).…”
Section: Resultsmentioning
confidence: 80%
“…CO 2 clathrate hydrates are involved in current potential applications in sustainable industries, such as CO 2 capture technologies, that are necessary to be developed to store this greenhouse gas [1–12] . Thus, both scientific and technological communities, from different fields of chemistry, physics, geology, engineering, etc., have devoted numerous collaborative research efforts, involving investigations at microscopic level using molecular simulation tools, as several processes (hydrate nucleation or growth or cage occupancy) could get hardly accessible though experimentation [12–23] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, aerogels have been used in adsorption [ 4 , 5 ], catalysts, supercapacitors [ 6 , 7 ], sensors [ 8 ], energy storage [ 9 ], and so forth. Over the past few decades, aerogels made from polymer have been developed, such as phenol-formaldehyde resin [ 10 ], polyurethanes [ 11 ], polyureas [ 12 ], polyamides [ 13 ], and polyimide [ 14 ]. Compared to other aerogels, PI aerogels attracted more attention from researchers due to perfect chemical stability [ 15 ], good mechanical properties [ 16 ], perfect dielectric performance [ 17 , 18 ] and high decomposition temperatures [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%